Escolítidos asociados en árboles de Tectona Grandis L.F. (teca) enfermos con marchitez vascular y muerte en la Provincia de Los Ríos, año 2018. - Castro Villares, Jefferson Javier. (2018)
The present research project was carried out in three study sites, Canbiosca in Buena Fe canton, Rafaelita cantón Ventanas and La Chorrera cantón Valencia, towns belonging to the Province of Los Ríos. The research objectives were to establish the incidence and severity of the disease, identify and determine abundance and diversity indices of associated scolitids in teak trees that showed symptoms of regressive death and vascular wilt. Three plots of 500 m2 were installed by study sites, where trees were identified that presented symptoms, then three diseased trees were removed and sectioned every four meters, followed by opening the wood for the collection of insects, which were deposited in flasks with 70 ° alcohol. Finally, the identification was carried out in the microbiology laboratory of the UTEQ with the help of a stereomicroscope and dichotomous keys. The most abundant scolithids were: Xyleborus ferrugineus, Hypothenemus sp and Premmobius cavipennis. The Shannon - Wiener index ranged from H'= 0.78 to 1.10 indicating that there is low diversity for the three sites. The Simpson index ranged from S = 0.46 to 0.61, indicating medium diversity. The Margaleff index showed greater richness in La Chorrera with a value of 0.64, which represents six species, and lower richness in Canbiosca with 0.28, which represents three species; the Chao-Jaccard similarity index was higher between the Canbiosca and La sites. Chorrera with Cj: 0.50, and Rafaelita presented less similarity with respect to the three sites.